The Effect of Emotional Intelligence on Peer Support for Students with Disabilities in Inclusive Junior High Schools in Semarang - Febrina Putri Adhani; Woro Apriliana Sari (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2026)
This study aimed to examine the effect of emotional intelligence among students without disabilities on their peer support for students with disabilities in inclusive junior high schools in Semarang City. Employing a quantitative approach with a multistage sampling method, the study involved 234 respondents selected through purposive sampling based on participant criteria and simple random sampling for school selection. Data were collected directly using an emotional intelligence scale and a peer support scale, and were subsequently analyzed using simple linear regression. The results indicated that emotional intelligence had a positive and significant effect on peer support (t = 10,912; p < 0,001), with an R² value of 0,339. This finding demonstrates that emotional intelligence accounted for 33,9% of the variance in peer support behavior. The findings suggest that emotional intelligence is an important determinant in fostering supportive social interactions within inclusive school environments.